EU LEGAL FRAMEWORK OF FIGHT AGAINST CHILD PORNOGRAPHY ON THE INTERNET - Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Sexual abuse and exploitation of children is a serious violation of the basic rights of a child and child pornography on the Internet represents specific harmful content, whose existence and expansion can not be possibly about the freedom of opinion and expression. The fight against child pornography on Internet includes criminalization of certain harmful behaviors, identification of children who are the victims, detection of the perpetrators of these crimes and their prosecution, termination of criminal networks, removal of pornographic content from the Internet or disable of access to the sites where these content are to be found. Although Internet is almost unlimited space for distribution of child pornographic material, the state’s response is territorially limited, due to the fact that even if the state sets control over content on Internet sites located within its territory, users can find material on the Internet sites that are located outside the reach of the authorities of that country. For this reason, the fight against online child pornography sets requirement for the harmonization of national legislation and the establishment of effective international cooperation.